Challenges and Reforms in the Accounting System of Ukraine: The Impact of War and Transition to International Standards - Bohušová, Hana (Publishing House of Wroclaw University of Economics and Business, 2025)
[This book highlights the lessons learned from the V4 countries and Ukraine, offering a comparative perspective on regulatory frameworks, enforcement mechanisms, and technological advancements in fraud detection. Each chapter examines a specific aspect of fraud detection, offering theoretical insights, empirical research and case studies that illustrate both the challenges and best practices in combating fraudulent activities. Chapter 1 explores the role of artificial intelligence (AI) in tax fraud detection. Chapter 2 investigates tax security and its vulnerabilities. In Chapter 3 the author focuses on occupational fraud, a major issue affecting both private and public sectors. Chapter 4 scrutinizes creative accounting practices, a deceitful technique used by businesses to manipulate financial statements. Chapter 5 studies Ukraine’s regulatory framework, the war’s effects on financial reporting, and the barriers to achieving accounting transparency. In Chapter 6 the author addresses the controversial issue of bank account blocking by tax authorities. Chapters 7 and 8 explore VAT fraud, particularly carousel fraud, one of the most damaging types of tax fraud in the EU. Chapter 9 shifts the focus to corporate anti-corruption efforts through non-financial reporting. Chapter 10 provides recommendations for fighting corruption, CIT fraud, PIT fraud, VAT fraud, money laundering and using AI and modern tools for preventing fraud. By bringing together academic research, policy analysis, and real-world case studies, this book aims to bridge the gap between theory and practice in fraud detection.] z zapowiedzi
Wroclaw: Publishing House of Wroclaw University of Economics and Business, 2025, s. 50-61
Keywords: tax fraud; fraud detection; bank account blocking; occupational fraud; carousel fraud